2022
DOI: 10.1080/21505594.2022.2078471
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis reveals a critical role for the WSSV immediate-early protein IE1 in modulating the host prophenoloxidase system

Abstract: White spot syndrome virus (WSSV) is a large, enveloped, double-stranded DNA virus that threatens shrimp aquaculture worldwide. So far, the mechanisms of WSSV-host interactions are ill-defined. Recent studies have revealed that IE1, an immediate-early protein of WSSV, is a multifunctional modulator implicated in virus–host interactions. In this study, the functions of IE1 were further explored by identifying its interacting proteins using GST-pull down and mass spectrometry analysis. A total of 361 host protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Knockdown of IE-1 reduced viral load and WSSV gene expression, while recombinant IE-1 inhibited host prophenoloxidase in a dose-dependent manner. 531 Metabolomic studies of gill, haemolymph and hepatopancreas have revealed clearly different profiles in WSSV infected and non-infected shrimp, consistent with changes in osmoregulation in the gills, upregulation of the glutathione pathway, increased production of an antimicrobial peptide itaconic acid in the hemolymph and a shift from aerobic to anaerobic metabolism as previously described. 532 Interestingly, some of the changes in the haemolymph (increased TCA intermediates and decreased amino acids) were similar to those in haemolymph of P. vannamei challenged with Vibrio parahaemolyticus 533 while some molecules were specific for each pathogen such as itaconic acid in WSSV-challenged shrimp and increased phosphoenolpyruvic acid (PEP) in shrimp exposed to V. parahaemolyticus, suggesting that there are pathogenspecific innate immune responses in shrimp.…”
Section: Proteomicssupporting
confidence: 77%
See 1 more Smart Citation
“…Knockdown of IE-1 reduced viral load and WSSV gene expression, while recombinant IE-1 inhibited host prophenoloxidase in a dose-dependent manner. 531 Metabolomic studies of gill, haemolymph and hepatopancreas have revealed clearly different profiles in WSSV infected and non-infected shrimp, consistent with changes in osmoregulation in the gills, upregulation of the glutathione pathway, increased production of an antimicrobial peptide itaconic acid in the hemolymph and a shift from aerobic to anaerobic metabolism as previously described. 532 Interestingly, some of the changes in the haemolymph (increased TCA intermediates and decreased amino acids) were similar to those in haemolymph of P. vannamei challenged with Vibrio parahaemolyticus 533 while some molecules were specific for each pathogen such as itaconic acid in WSSV-challenged shrimp and increased phosphoenolpyruvic acid (PEP) in shrimp exposed to V. parahaemolyticus, suggesting that there are pathogenspecific innate immune responses in shrimp.…”
Section: Proteomicssupporting
confidence: 77%
“…In P. vannamei, GST-pull down and mass spectrometry analysis were used to investigate the interaction of the immediate-early WSSV protein (IE-1) with shrimp proteins, finding 361 host proteins that could potentially bind to IE. 531 Most of these proteins were involved in signalling pathways such as the prophenoloxidase (proPO), PI3K-AKT, MAPK, focal adhesion, and cell cycle systems. Knockdown of IE-1 reduced viral load and WSSV gene expression, while recombinant IE-1 inhibited host prophenoloxidase in a dose-dependent manner.…”
Section: Proteomicsmentioning
confidence: 99%
“…IE1, which is an IE protein of WSSV, is a multifunctional regulator that plays critical roles in virus–host interactions. It not only functioned as a transcription factor [ 22 ], but also interacted with various shrimp cellular proteins (i.e., Rb, STAT, JNK, β-catenin, Chibby, and proPO) to manipulate the host cellular functions for viral genome replication [ 18 , 19 , 23 , 24 , 25 , 26 ]. In this study, RNAi coupled with transcriptome sequencing were conducted to explore the downstream genes that are regulated by IE1 directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…High-Five (BTI-TN-5B1-4) cells were seeded on a 24-well cell culture plate and maintained in Express Five SFM medium (Invitrogen, Waltham, MA, USA) overnight. For plasmid transfection, the IE1 expression plasmid pIZ-V5-IE1 (1 µg), which was constructed in our previous study [ 26 ], was transfected into cells using the FuGENE HD transfection reagent (Promega, Madison, WI, USA) following manufacturer’s instructions. An equal amount of empty vector pIZ-V5-His (Invitrogen, Waltham, MA, USA) was transfected and used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation